KAJIAN DAERAH RENDAMAN TSUNAMI DI PESISIR TELUK LAMPUNG AKIBAT PERUBAHAN TOPOGRAFI GUNUNG ANAK KRAKATAU DI TAHUN 2018 - Resti Elida Nurhawati Siregar; Ahmad Zakaria; Armijon Armijon (Jurnal Geofisika Eksplorasi, 2020)
The eruption of the Anak Krakatoa volcano (GAK) in December 2018 caused part of the body of GAK to collapse into the sea and caused a tsunami. This avalanche also caused changes in the topography of GAK. If there is a repeat of the disaster with the current GAK topography, it will certainly cause changes in tsunami wave height at the shoreline which will affect changes in the tsunami inundation area. Because the location of the Lampung Bay coastal area which is quite close to GAK makes the Lampung Bay coastal area vulnerable to the tsunami disaster. So, it is necessary to study the tsunami inundation area due to changes in the current GAK topography in the coastal area of Lampung Bay. This study was conducted using non-numerical methods to obtain wave heights at the shoreline and the Berryman methods to obtain tsunami inundation areas in the coastal areas of Lampung bay by making three scenarios. Based on the results of the study, it is known that the height of tsunami waves, which are 13 meters, 26 meters, and 39 meters with an average time of arrival of tsunami waves on the shoreline is 57 minutes. Where there are seven sub-districts submerged by the tsunami with a distance of about 160 meters to 1.6 kilometers.